Zinc oxide nanoparticles as additives for improved dimensional accuracy in vat photopolymerization - Ng, Chin Siang (2022)
To improve the dimensional accuracy of 3D printed parts produced by vat photopolymerization, a controlled light penetration through the photopolymer resin is necessary to avoid excessive unwanted curing caused by overexposure. Although photoabsorbing additives like Sudan I can attenuate light to decrease excessive light penetration, they also require longer exposure time to solidify the resin. In this work, photocatalytic zinc oxide nanoparticles (ZnONP) were used as resin additives substituting photoabsorbers to control overexposure that causes loss in dimensional accuracy. Compared to adding 0.1 wt/wt% of Sudan I, adding 2.5 wt/wt% of ZnONP not only showed similar level of control in light penetration, but reduced the required curing time of the resin. Significant improvement in preventing unwanted curing was also observed in resin with ZnONP, as evident by our printing tests on open channels and overhanging structures. Unlike Sudan I which deteriorated the mechanical properties of printed parts, ZnONP additives have rendered more effective curing that resulted in improved tensile strength, fracture strain and Young's modulus.